2016
DOI: 10.2139/ssrn.2879417
|View full text |Cite
|
Sign up to set email alerts
|

Mother's Education and Increased Child Survival in Madagascar: What Can We Say?

Abstract: This paper aims to assess whether a causal effect exists between maternal education and child survival in Madagascar. The omission of factors such as mother's health, innate ability and time preferences could lead to an overestimation of the true effect of education. The case of sub-Saharan Africa where child mortality rates are the highest, is overlooked by most of the causal evidence gathered so far for developing countries. The present paper attempts to redress this omission through the adoption of a carefu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The choropleth in Figure 5 shows that the spatial pattern depicted by education changes significantly over time; this also agrees with the study by De Onis et al 4 and Badji 1 , which revealed that education has a significant negative effect on U5M over time. Generally, the highest effect of education is in the North, North-West, and the West of the country in the years 2009 and 2014.…”
Section: Resultssupporting
confidence: 89%
“…The choropleth in Figure 5 shows that the spatial pattern depicted by education changes significantly over time; this also agrees with the study by De Onis et al 4 and Badji 1 , which revealed that education has a significant negative effect on U5M over time. Generally, the highest effect of education is in the North, North-West, and the West of the country in the years 2009 and 2014.…”
Section: Resultssupporting
confidence: 89%
“…It is expected that the educational qualification of parents increases; it would increase the survival status of children. As evidence shown in prior studies, the high mothers' education level has resulted in increasing the maternal awareness about infant health and hygiene facilities, hereby resulted in the decline of under-five mortality rates in sub-Saharan African countries [20], Malawi and Uganda [21], Madagascar [22], Tanzania [23], and Nigeria [24]. Based on a systematic review and metaanalysis, a study was undergone in Ethiopia on the effects of maternal education on infant mortality which indicated that infants born from mothers who had attended primary education was associated with a 28% reduction in the odds of infant mortality compared to those infants born from mothers who were illiterate [25]; in the current study, it shows 18% reduction.…”
Section: Discussionmentioning
confidence: 83%
“…We found that households with higher educational levels (women and husbands) are more likely to provide institutional care. Previous research has found similar determinants of institutional delivery [12][13][14][15][16][17][18][19]. Parents' educational qualifications and the survival status of their family members are also associated factors.…”
Section: Discussionmentioning
confidence: 86%
“…In Ethiopia and Malawi, the usage of institutional facilities was poor relative to most Sub-Saharan African countries [11]. Non-users of medical facilities made the most significant contribution during pregnancy and childbirth, as well as highest maternal mortality rate was observed in Malawi [12]. Even if increased institutional delivery reduces maternal and neonatal mortality rates, distance, inaccessibility, and a lack of appropriate facilities make it more difficult [3].…”
Section: Discussionmentioning
confidence: 99%